Model identification and control of prosthetic leg. (December 2020) - Adarsh, S R; Selvakumar, S
Abstract: Prosthesis is an artificial device that replaces missing body parts due to trauma, disease / accident. Prosthesis are mainly intended for restoring the normal functions of moving body part. Double pendulum structure is taken into consideration for modelling the system. In this system thigh and shank represents the pendulum links. Hip and knee joints create linkage between upper part of the body through thigh and shank. The muscles of both thigh and shank are initiated by external torques provided by stepper motor at hip and knee joints. The process variable to be controlled in the system is the position of both hip and knee. The work deals with the identification of system model along with the implementation of controllers like PID controller, Sliding mode controller (SMC) and Linear quadratic regulatory (LQR) controller and Linear quadratic tracking (LQT) controller. The results are compared.